CEO duality: Newspapers and stock market reactions - Marco Caiffa; Vincenzo Farina; Lucrezia Fattobene (Journal of Risk and Financial Management, 2021)
This study aims to investigate the unsettled issue of the relationship between CEO duality and a firm's value through the perspective of investors' reaction to news which mention apical directors with a single role and Board Chair CEOs. With a unique and hand-collected database of 60,805 newspaper articles, text-analysis, event-study and regression analysis methodologies were applied to capture news sentiment and study the direction and the magnitude of the stock market reaction. Results reveal that news mentioning Board Chair CEOs are negatively processed by investors, revealing a negative perception by investors about CEO duality. The study provides empirical support for the agency theory, in contrast to the stewardship theory, in the interpretation of CEO duality. It also proposes the methodology of systematically quantifying language to explore corporate governance issues and their link with financial markets.
Keywords: 330; CEO duality; corporate governance; mass media; sentiment; stock-market; text-analysis; event-study; agency theory; stewardship theory